Efektivitas Penggunaan Game Edukasi Wordwall dan Motivasi Terhadap Hasil Belajar Peluang Kejadian - Aluna, Fiki Nanda; Rakhmawati, Nahlia; Rahman, Fatchiyah (Universitas Dr. Soetomo, 2025)
Abstract The wordwall educational game is a digital game-based learning application that has various quiz features with a combination of colors, moving images, and sounds that can be used by educators in learning. Wordwall educational games can also motivate students to learn. Learning motivation is the overall driving force within students to drive behavioral changes that lead to learning activities to improve their learning outcomes so that the expected educational goals are achieved. The aims of this study is to determine the effect of the use of wordwall educational games to motivatived partially or together on the mathematics learning outcomes of SMKN Mojoagung class X AKL 3 students on the material of event probability. This study is a quantitative study. The population in this study were all class X AKL students of SMKN Mojoagung. The research data were taken using a questionnaire on the use of wordwall educational games, a questionnaire on learning motivation and a learning outcome test that had been validated. The data analysis technique used multiple linear regression tests consisting of classical assumption tests and hypothesis tests. Based on the results of the study, it can be concluded that there is an influence of the use of wordwall educational games on the learning outcomes of the probability of occurrence, there is an influence of motivation on the learning outcomes of the probability of occurrence and there is an influence of the use of wordwall educational games and motivation on the learning outcomes of students' probability of occurrence. Keywords: Wordwall Educational Games, Learning Outcomes, Motivation, probability of occurrence. Abstrak Game edukasi wordwall merupakan sebuah aplikasi pembelajaran berbasis game digital yang memiliki berbagai fitur kuis dengan kombinasi warna, gambar bergerak, dan suara yang dapat dimanfaatkan oleh pendidik di dalam pembelajaran. Game edukasi wordwall juga dapat memberikan motivasi kepada siswa dalam belajar. Motivasi belajar adalah keseluruhan daya penggerak di dalam diri siswa untuk menggerakan perubahan tingkah laku yang menimbulkan kegiatan belajar untuk meningkatkan hasil belajarnya sehingga tercapai tujuan pendidikan yang diharapkan. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan game edukasi wordwall untuk memotivasi siswa baik secara parsial maupun bersama-sama terhadap hasil belajar matematika siswa SMKN Mojoagung kelas X AKL 3 pada materi peluang kejadian. Penelitian ini merupakan penelitian kuantitatif. Populasi dalam penelitian ini adalah seluruh siswa kelas X AKL SMKN Mojoagung. Data penelitian diambil menggunakan angket penggunaan game edukasi wordwall, angket motivasi belajar dan tes hasil belajar yang telah divalidasi. Teknik analisis data pada penelitian ini menggunakan uji regresi linear berganda yang terdiri dari uji asumsi klasik dan uji hipotesis. Berdasarkan hasil penelitian dapat disimpulkan bahwa ada pengaruh penggunaan game edukasi wordwall terhadap hasil belajar peluang kejadian, ada pengaruh motivasi terhadap hasil belajar peluang kejadian dan ada pengaruh penggunaan game edukasi wordwall dan motivasi terhadap hasil belajar peluang kejadian siswa. Kata Kunci : Game Edukasi Wordwall, Hasil Belajar, Motivasi, peluang kejadian.